Impact of nicotine-free and nicotine-rich flavored electronic cigarette refill liquids on primary human melanocyte function - Shilpi Goenka (Toxicology Reports)
In this study, five popular EC liquid flavors–strawberry, banana, vanilla, tobacco, and menthol–were examined on human melanocyte functions. Each flavored e-liquid (in 80/20 PG/VG vehicle) was tested without or with 18 mg/mL nicotine. The effects of PG/VG and nicotine-containing vehicles were also evaluated. Results revealed that nicotine-free and nicotine-containing e-liquids had comparable cytotoxicity, with menthol> > banana> tobacco> vanilla> strawberry. This cytotoxicity was unrelated to either nicotine or the vehicle. PG/VG (1 and 2 %) increased melanin production without influencing cellular tyrosinase activity. The flavored e-liquids did not further affect melanin production, suggesting that the vehicle's effect, not the flavor, was responsible for the increased melanin production. Interestingly, nicotine at 2 % in the vehicle restored the stimulated melanin production to the control. Flavors suppressed cellular tyrosinase activity, with vanilla and banana flavors robustly inhibiting it. Vanilla and banana e-liquids also enhanced reactive oxygen species (ROS) production, which did not originate from the vehicle or nicotine-containing vehicle. Banana e-liquid with nicotine lowered ROS generation compared to nicotine-free banana e-liquid. Common flavors in e-liquids can cause cytotoxicity and influence melanogenesis even without nicotine, indicating that the use of ECs may not completely avoid the harmful effects of cigarette smoking. Further studies are warranted to investigate e-liquid aerosol effects on melanocytes.